PAK Membrane Translocation and Phosphorylation Regulate Platelet Aggregation Downstream of Gi and G12/13 Pathways - Zhang, Jianjun; Zhang, Yan; Zheng, Shuang; Liu, Yangyang; Chang, Lin; Pan, Guanxing; Hu, Liang; Zhang, Si; Liu, Junling; Kim, Soochong; Dong, Jianzeng; Ding, Zhongren (Thrombosis and Haemostasis, 2020)
Platelet activation plays a pivotal role in physiological hemostasis and pathological thrombosis causing heart attack and stroke. Previous studies conclude that simultaneous activation of Gi and G12/13 signaling pathways is sufficient to cause platelet aggregation. However, using Gq knockout mice and Gq-specific inhibitors, we here demonstrated that platelet aggregation downstream of coactivation of Gi and G12/13 depends on agonist concentrations; coactivation of Gi and G12/13 pathways only induces platelet aggregation under higher agonist concentrations. We confirmed Gi and G12/13 pathway activation by showing cAMP (cyclic adenosine monophosphate) decrease and RhoA activation in platelets stimulated at both low and high agonist concentrations. Interestingly, we found that though Akt and PAK (p21-activated kinase) translocate to the platelet membrane upon both low and high agonist stimulation, membrane-translocated Akt and PAK only phosphorylate at high agonist concentrations, correlating well with platelet aggregation downstream of concomitant Gi and G12/13 pathway activation. PAK inhibitor abolishes Akt phosphorylation, inhibits platelet aggregation in vitro and arterial thrombus formation in vivo. We propose that the PAK-PI3K/Akt pathway mediates platelet aggregation downstream of Gi and G12/13, and PAK may represent a potential antiplatelet and antithrombotic target.
Keywords: platelets; thrombosis; Gi; G12/13; Akt; PAK